Peran Guru dalam Menumbuhkan Kemandirian Anak Usia 5-6 Tahun di Sekolah Indonesia Kuala Lumpur - Afifah, Dwinta Nuha; Kurnia Jayadinata, Asep; Ardiyanti, Dhea; Siswanto, Budi; Rupinis (Jurnal Pendidikan (Teori dan Praktik), 2026)
This study aims to explain the role of teachers in fostering the independence of children aged 5-6 years. The purpose of this study is to examine teachers' roles in fostering independence among children aged 5-6 years. Children's independence is an important aspect of development closely related to problem-solving skills and the formation of a responsible, confident character. This study uses a qualitative case study approach. Data were obtained through observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman's interactive model. The findings of this study show that teachers serve as facilitators, role models, encouragers, and consistent rule-makers to instill independent habits in children. The steps taken include providing real examples, providing verbal encouragement, positive appreciation, and providing opportunities for children to complete tasks independently. Simple activities such as eating, putting on shoes, buttoning clothes, and tidying up toys are practical for developing a sense of responsibility and problem-solving skills. This study emphasizes the importance of consistency in habituation, a supportive environment, and cooperation between teachers and parents to increase children's independence from an early age